(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we consider a singularly perturbed convection-diffusion problem. The problem involves two small parameters that gives rise to two boundary layers at two endpoints of the domain. For this problem, a non-monotone finite element methods is used. A priori error bound in the maximum norm is obtained. Based on the a priori error bound, we show that there exists Bakhvalov-type mesh that gives optimal error bound of O(N^−2) which is robust with respect to the two perturbation parameters. Numerical results are given that confirm the theoretical result.